Activation of AKT/mammalian target of rapamycin signaling in the peripheral blood of women with premature ovarian insufficiency and its correlation with FMR1 expression - Rehnitz, Julia; Messmer, Birgitta; Bender, Ulrike; Nguyen, Xuan Phuoc; Germeyer, Ariane; Hinderhofer, Katrin; Strowitzki, Thomas; Capp, Edison (Reproductive biology and endocrinology, 2022)
The protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway regulates early follicular activation and follicular pool maintenance in female germline cells. Fragile X mental retardation 1 (FMR1) regulates folliculogenesis and it is variably expressed in patients with Premature Ovary Insufficiency. FMR1 expression is supposed to be linked to AKT/mTOR signaling in an ovarian response dependent manner as demonstrated in recent in vitro and in vivo studies in the female germline in vitro and in vivo.